ETHNIC PUBLIC ORGANIZATIONS IN KHAKASSIA - Medvedeva T.N.; Troyakova Y.K. (Scientific Journal of Pedagogy and Economics, 2020)
The purpose of the study of the legal basis for the activities of ethnic public organizations in Khakassia as exemplified by the Khakass regional public movement of the Khakass people. We study the characteristics of the organizational structure of ethnic public organizations. The author’s position is proposed related to the amendment of existing legislation. Significantly the importance of public associations is increased, since they are not only a means of spiritual unification of ethnic groups, but also help to mitigate national contradictions on the basis of cooperation between the relevant ethnic group and the authorities, with other ethnic groups, these most important factors contribute to the formation of a tolerant attitude to the socio-cultural identity of each nation. To clarify more deeply the various wordings of the analyzed regulatory provisions the study uses the legal method. Also applied are the methods of historicism, sociocultural determinism, synchronization and diachronization. In addition, a comprehensive and systematic comparative-historical analysis, chronologization, classification and typology of public organizations are used. As a promising method, a retrospective analysis is implemented, which allows you to study life activity and functioning of social organizations of ethnic orientation in evolution. The authors conclude in the subject of the Russian Federation practically established a regional regulatory – legal framework governing the activity of public organizations of ethnic orientation. It requires the publication of a comprehensive federal law regulating important issues of national, cultural, linguistic revival of the indigenous peoples of Southern Siberia.